Decolonising public service television in Aotearoa New Zealand: telling better stories about Indigenous rurality. (May 2023) - Fountaine, Susan; Bulmer, Sandy; Palmer, Farah; Chase, Lisa
In settler-colonial countries like Aotearoa New Zealand, television programmes about rurality are fundamentally entwined with the nation's colonial history, but how this context impacts on locally made, public service television content and production is seldom examined. Utilising data collected from interviews with programme makers and a novel bi-cultural friendship pair methodology, we examine how a high-rating mainstream programme, Country Calendar, conceptualises and delivers stories about Indigenous Māori and consider the extent to which these stories represent a decolonising of television narratives about rurality. The findings highlight the importance of incorporating Indigenous voices and values, the impact of structural limitations and staffing constraints on public service television's decolonising aspirations, and challenges reconciling settler-colonialism with the show's well-established 'rosy glow'. While rural media are often overlooked by communication scholars, our study demonstrates the contributions they might make to the larger task of decolonising storytelling about national identity.